Evaluation of the determination of hotel room rental rates for case studies at Ros-in Yogyakarta hotels - Ditya, Dicky Kurnia (Institute of Accounting Research and Novation (IARN), 2023)
The purpose of this study was to evaluate the room rental rates set by Hotel Ros-In Bantul. The evaluation was carried out by comparing the room rental rates set by the Ros-In Hotel with the room rental rates calculated by the researcher. The room rental rate calculation method used is the same room rate calculation method as Hotel Ros-In Bantul. The method used by Hotel Ros-In Bantul is the Break Even Point (BEP) method. This type of research is a case study The data obtained from Hotel Ros-In is data obtained from interviews and documentation without being able to prove the truth. The results showed that there was a difference between the room rental rates set by Hotel Ros-In and the room rental rates studied by researchers using the same calculation method, namely the BEP method. The difference in room rental rates using the BEP method is 5.24% for the Standard room type, 6.23% for the Deluxe room type, and 17.56% for the Suite room type. Using the Rule of Thumb method, it was also found that the difference in room rates was 4.89% (Ros-In Hotel room rates > Room rates for the Rule of Thumb method). After conducting a t-test to debate the difference in hotel room rental rates found using the BEP method, it can be concluded that there is no difference between the room rental rates calculated using the BEP method and the room rental rates of the Ros-In Hotel.